ADDITION OF ADJUVANTS IN RECOMBINANT SUBUNIT VACCINES FOR THE PREVENTION OF GROUPER SLEEPY DISEASE IRIDOVIRUS (GSDIV) INFECTION IN HUMPBACK GROUPER, Cromileptes altivelis - Ketut Mahardika; Indah Mastuti; Ahmad Muzaki; Sudewi Sudewi (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2016)
Infection of grouper sleepy disease iridovirus (GSDIV) which is a member of Megalocytivirus causes mass mortalities in marine fish in Indonesia. This study was conducted to know the effectiveness of recombinant subunit vaccine of GSDIV with an addition of adjuvants against GSDIV infection. Inactive bacteria Eschericia coli containing recombinant MCP-GSDIV protein was added with montanide ISA adjuvant at a ratio of 3:7. The vaccine was administered to humpback grouper, Cromileptes altivelis by intramuscular and intraperitoneal injection at a dose of 0.1 mL/fish. Test of the vaccine in humpback grouper was performed in four replicates (four trials). Results of the vaccination showed that the recombinant protein vaccine added with the adjuvant increased immunity of humpback grouper, indicated by higher relative percent survival (RPS= 77.78%) compared to negative control (PBS) and 50% higher compared to protein control (pET Sumo CAT) at two weeks post vaccination. The RPS values of the recombinant protein vaccine were still higher (53.57%-72.73%) than those of the control vaccine and 25%-53.33% of the protein control in the 4th week post vaccination. GSDIV detection by PCR showed that MCP-GSDIV-DNA and pET Sumo CAT-DNA were not detected in the vaccinated fish after one, two, three, and four weeks post vaccination. The fish died in both of vaccinated and control groups after experimental challenge with GSDIV were found to be infected with GSDIV. It can be stated that recombinant subunit vaccine of GSDIV with the addition of montanide ISA adjuvant could be used to prevent and diminish mortalities of grouper against GSDIV infection.